EFFECT OF SELF EFFICACY AND PRIOR KNOWLEDGE ON STUDENTS’ SKILLS - Ryan Permana; Febrianto Sabirin; Vindo Feladi (STKIP Singkawang, 2016)
This research aims to determine: (1) Information about the information of self-efficacy, prior knowledge, and skills of students in the subject of Advanced Computer Network course in Information and computer technology education IKIP PGRI Pontianak, (2) The effect of self efficacy on the skills of students in the subject of Advanced Computer Network course in Information and computer technology education IKIP PGRI Pontianak, (3) Effect prior knowledge of the skills of students in the subject of Advanced Computer Network course in Information and computer technology education IKIP PGRI Pontianak, and (4) The effect of self-efficacy and prior knowledge of the skills of students in the subject of Advanced Computer Network course in Information and computer technology education IKIP PGRI Pontianak. This research is an ex-post facto research with correlation design. The independent variable in this research were self efficacy (X 1) and prior knowledge (X 2). While the dependent variable in this research is the students' skills (Y). The sample in this research were 108 students of Information and computer technology education IKIP PGRI Pontianak. The analysis technique used is simple regression analysis, and multiple regression analysis. Results of the research: (1) The level of prior knowledge of students of 79 146 at intervals of 50.70 - 99.99, the level of self-efficacy of students at 56.45 with intervals of 48-65, and the skill level of students at 72.38 with intervals of 51.50 - 81.50. (2) there are significant positive and significant correlation between self efficacy against students' skills by 9.2%. (3) there is a positive and significant influence between the prior knowledge the students' skills of 10.7%. (4) there are significant positive and significant correlation between self-efficacy and prior knowledge the students' skills of 17.4%.